CARDIOVASCULAR RISK FACTORS PROFILE OF YOUNG PATIENTS WITH CORONARY ARTERY DISEASE: THE YOUNG HEART STUDY - A Adhikari; R Nahrwold; G Vaidean; R Hentz; S De Jesus; N. Swe; D Gaballa; J Fishbein; C Wutawunashe; E Gianos (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Factors Background: The increasing trends in acute myocardial infarction among the young suggest potential increases in specific cardiovascular risk profiles. As traditional risk calculators underperform in the younger groups, early identification of specific risk factors and therapeutic management are critical. We sought to evaluate traditional and non-traditional risk factors in this population, rates of guideline-directed therapy and the impact of a risk reduction program on residual risk. We report the baseline characteristics of this population. Methods: We enrolled 60 patients, ≤59 years old, with angiographically proven coronary artery plaque and at least two uncontrolled risk factors: BMI>25 kg/m2, A1C >7% in diabetic patients and >5.6 in those without, systolic blood pressure >130 mmHg, LDL>70 mg/dL, smoking. These cross-sectional, baseline data were collected through structured questionnaires on socio-demographic and lifestyle factors, blood samples, and angiographic data. Continuous variables were analyzed using median and quartiles (Q1-Q3) and the Wilcoxon rank-sum test. Categorical variables were analyzed using frequency (percentage) and the Chi-Square or Fisher's Exact test. Results: The median age (Q1-Q3) was 51 (45-55), 70% were male, 46.7% were white. 76.7% had hypertension, 91.7% had hyperlipidemia, 36.7% had diabetes, 28.3% had prediabetes, 88.3% had obstructive CAD and 38.3% had a history of myocardial infarction. The median (IQR) BMI was 28.8 (26.8-33.8), SBP 129 mmHg (121-138), LDL 69 mg/dL (53-96), Lp (a) 57.8 nmol/L (19.8-129.6), HbA1c 6.1% (5.5-7.5), hsCRP 1.25 mg/L (0.60-4.45), TMAO 2.95 µmol/L (1.9-5.2).Uncontrolled risk factors were prevalent: gender-specific waist circumference goals were unmet in 54.6%, metabolic syndrome in 60%, 47.5% had an LDL >=70, 42.4% had Lp(a) >=75nmol/L, 41.7% had hsCRP >=2, 28.3% had suboptimal TMAO, 68.2% of diabetics had an HbA1c >=7% and 26.7% were either current smokers or had quit smoking within the last year. Only 83% of the patients were on antiplatelet therapy, and 70% were on a guideline dose of statin. Conclusion: These data from the Young Heart study suggest a high prevalence of cardiometabolic disease related to obesity/overweight and abnormal glucometabolic state. However, entry criteria may also dictate these findings. Interestingly, elevated CRP, elevated TMAO and Lp(a) were high and may warrant future investigation.